HUBUNGAN ANTARA KESADARAN DIRI DAN PENYESUAIAN DIRI DENGAN KEDISIPLINAN MENERAPKAN PROTOKOL KESEHATAN DI ERA NEW NORMAL - Novita Sari; Nanik Kholifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Currently, all countries in the world are experiencing disaster, namely Covid-19 including Indonesia. Government has imposed restrictions by imposing a new normal policy. However, the positive number of Covid-19 is still soaring in May-July 2021, this is presumably due toÂ industrial sector is still open as usual, where employees who work violate the rules that have been set. Thus this is related to employee discipline in complying with health protocols. This study aims to determine the relationship of self-awareness and adjustment to the discipline of using health protocols in the normal era. Subjects in this study were 84 employees of PT. Duta Beton Mandiri, using accidental sampling as a sampling technique. Data collection uses a discipline scale, self-awareness scale, and self-adjustment scale. Discipline scale there are 36 items with reliability of 0,898, self-awareness scale there are 34 items with reliability of 0,911, and self-adjustment scale, there are 36 items with reliability of 0,891. Data analysis technique using multiple regression analysis. From calculation results, F value is 31,532 with p = 0,000 (p Ë‚ 0,05), so there are is a very significant correlation between self-awareness and self-adjustment to discipline of using health protocols in the new normal era. Thus self-awareness and adjustment affect individuals in applying the discipline of health protocols.